Analysis of the customer- based efficiency at workplace for tourism industry using house of quality - Dinçer, Hasan; Yüksel, Serhat (IGI Global, 2019)
The aim of the study is to evaluate the customer expectations and workplace efficiency of tourism industry in the competitive market environment. For this purpose, house of quality is applied to measure the relative importance of the customer expectations and to rank the workplace efficiency based on customer needs using the fuzzy systems. A set of criteria for the customer expectations and workplace efficiency is defined with the supported literature to weight and rank the factors. Fuzzy DEMATEL is applied for weighting the criteria and fuzzy VIKOR is used for ranking the technical factors of competitive tourism industry. The findings show that tourism companies should mainly focus on designing services for the customers to use easily. In this context, website of the tourism companies should be redeveloped so that the users should understand all details regarding the tourism companies much easily. In addition, technological competency should be provided by the tourism companies to increase their competitive power.
Keywords: Decision Making; Industry; Decision-Making Trial